2010
DOI: 10.1016/s1836-9553(10)70040-0
|View full text |Cite
|
Sign up to set email alerts
|

Ground walk training improves functional exercise capacity more than cycle training in people with chronic obstructive pulmonary disease (COPD): a randomised trial

Abstract: Ground walk training increased endurance walking capacity more than cycle training and was similar to cycle training in improving peak walking capacity, peak and endurance cycle capacity and quality of life. This study provides evidence for ground walking as a mode of exercise training in pulmonary rehabilitation programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 30 publications
0
53
0
3
Order By: Relevance
“…Furthermore, exercising the patients' walking skills might be more effective to the patient than exercising cycling skills that are unlikely to be essential to everyday life. A recent study has even shown that supervised, progressive walking training resulted in a significantly larger increase in endurance walking capacity compared to supervised, progressive stationary cycle training [34]. Similar effects were found on peak walking and cycling capacity, endurance cycling capacity and health-related quality of life.…”
Section: Cycle-based Versus Walking-based Endurance Trainingmentioning
confidence: 74%
See 1 more Smart Citation
“…Furthermore, exercising the patients' walking skills might be more effective to the patient than exercising cycling skills that are unlikely to be essential to everyday life. A recent study has even shown that supervised, progressive walking training resulted in a significantly larger increase in endurance walking capacity compared to supervised, progressive stationary cycle training [34]. Similar effects were found on peak walking and cycling capacity, endurance cycling capacity and health-related quality of life.…”
Section: Cycle-based Versus Walking-based Endurance Trainingmentioning
confidence: 74%
“…reference point that was used in several studies [34,35] was to set the walking speed at ,80% of peak V9O 2 , which was achieved in a shuttle walking test. To avoid the complex and time consuming procedure of a ergospirometry during the shuttle walk test, peak V9O 2 can be approximately derived by the following equation: peak V9O 2 mL?min -1 ?kg -1 5 4.19+0.0256ISWT distance [36].…”
Section: Table 3 Practical Indications For Considering the Use Of An mentioning
confidence: 99%
“…Responsiveness of the ISWT Three studies were explicitly designed to evaluate the responsiveness to treatment of the ISWT, following bronchodilation [206], ambulatory oxygen therapy [219] or pulmonary rehabilitation [232]. Characteristics of the included studies can be seen in table S32.…”
Section: Measurements and Reporting For Iswtmentioning
confidence: 99%
“…Seven studies were specifically designed to examine the responsiveness of the ESWT to bronchodilation [105][106][107], oxygen therapy [219,233] and pulmonary rehabilitation [232,234]. The responsiveness of the ESWT was moderate to high, with standardised response means (mean change/standard deviation of change) ranging from 0.52 to 1.27.…”
Section: Responsiveness Of the Eswtmentioning
confidence: 99%
“…Secondly, oxygen-dependent individuals were ineligible to participate in this study, and the conclusions should not be uncritically applied to this subset. Thirdly, other exercise modalities which require no exercise apparatus, like Nordic walking and ground walking, have also been shown to improve exercise performance in individuals with COPD [41,42]. Finally, interdisciplinary pulmonary rehabilitation programmes can address specific issues, such as nutritional modulation, collaborative self-management to promote selfefficacy, advance care planning, and/or smoking cessation, which are not addressed during a course of t'ai chi.…”
mentioning
confidence: 99%